Addresing singularities of family business performance under the lenses of innovation and internationalization - Castro, Rafael Luís Barros (2021)
The main purpose of this dissertation is to explore and analyse the relationship between innovation and internationalization in family firms. Due to the individual character of this type of business, the processes of innovation and internationalization are depicted as being unique to the rest. To appraise the research, question the analysis was broken down into four parts: first of all, understanding the role of capital ownership in firms towards innovative and internationalisation attitudes. Secondly, understanding singularities of determinants to innovate in either family and non-family businesses, the same procedure was implemented for internationalisation and finally, appraising the self-reinforcement of the two vectors. As a result of shortage of literature regarding the biunivocal relation of these concepts it is pertinent to carry out an empirical study taking into account the Portuguese manufacturing industry. based on a panel sample of 41347 familyfirms and 23720 non family-firms, in the period between 2014 and 2017. The results provided evidence on positive connection between innovation and internationalization efforts in family owned businesses, although having a greater budget constraint they have a great profitability and effectiveness in their developments and procedures validating the existing literature, and shedding some light to the Portuguese context.